THEORETICAL AND PRACTICAL ASPECTS OF MONITORING THE FINANCIAL CONDITION OF AGRARIAN SECTOR ENTERPRISES - Zhakisheva, K.M.; Zhumanova, D.T. (Academic Journal of Physical and Chemical Sciences, 2018)
According to the authors, in Kazakhstan, as in any country in the world, diagnostics and constant monitoring of the stability of the financial condition of enterprises is an objective necessity in the framework of effective economic development of the state. Due to the crisis in the global economy, part of competitive enterprises are currently experiencing financial difficulties, which creates risks of bankruptcy, failure to fulfill obligations to creditors, investors and counterparties, failure to fulfill tax liabilities, adversely affects the loan portfolio of banks. In this regard, a complex assessment acquires particular relevance, that is, monitoring the financial status of enterprises in the agrarian sector of the economy of the Republic of Kazakhstan, whose main task is, first of all, to identify bankruptcy risks, the causes and factors for reducing the financial condition of enterprises in the agrarian sector.